Impact of Nd2O3 on physical properties of lead borate glass system - Marzuki, Ahmad; Astuti, Retno Willy; Fausta, Devara Ega; Kasy, Fransisca Indraningsih; Mahasindi, Melya Ayu (Journal of Physics: Theories and Applications, 2023)
The Nd2O3 doped lead borate glass with composition 45B2O3-(40-x)PbO-11ZnO-4Na2O-xNd2O3 (x=0; 0.5; 1.0; 1.5; 2.0; 2.5) mol% were fabricated using melt quenching method at 950oC for 35 minutes. The characterization of physical properties of glasses doped Nd2O3 were measured by density (ρ) based on the Archimedes principle. The other physical parameters such as molar volume (Vm), oxygen packing density (OPD), polaron radius (rp), ionic radius (ri), field strength (F), molar refraction (Rm), and metallization (Mn) were calculated using equation which derived from density. According to the measurement, the density of glasses decreased from 5.774 to 4.527 gr/cm3 while molar volume oppositely increased from 23.17 to 30.18 cm3/mol due to  atomic mass of Nd (144.24) smaller than Pb (207.2). Along with the increase of molar volume, there were decreasing of the OPD, the polar radius (1.731 －1.095) Å and the ion radius (4.296－2.717) Å iof glasses Meanwhile, the field strength and metallization properties of the glasses  increased as a result of the reduction rp and ri. The investigation of molar refractive shows an increasing trend because the addition of the concentration Nd2O3.